Несломленные: [о большевиках - депутатах IV Государственной Думы Г. И. Петровском, А. Е. Бадаеве, М. К. Муранове, Ф. Н. Самойлове, Н. Р. Шагове] / И. М. Дажина - Дажина Ирина Мартиновна (Политиздат, 1986)
Экземпляры: КХ (20160402) / Инвентарный номер: 868656 / Цена: 0.55 / Сис.шифр: 3КП1(092) / Авт.знак: Д 14 / ГРНТИ: 11 / ББК: 66